Dating placentalia: Morphological clocks fail to close the molecular fossil gap. (6th April 2016) - Puttick, Mark N.; Thomas, Gavin H.; Benton, Michael J.
Abstract : Dating the origin of Placentalia has been a contentious issue for biologists and paleontologists. Although it is likely that crown‐group placentals originated in the Late Cretaceous, nearly all molecular clock estimates point to a deeper Cretaceous origin. An approach with the potential to reconcile this discrepancy could be the application of a morphological clock. This would permit the direct incorporation of fossil data in node dating, and would break long internal branches of the tree, so leading to improved estimates of node ages. Here, we use a large morphological dataset and the tip‐calibration approach of MrBayes. We find that the estimated date for the origin of crown mammals is much older, ∼130–145 million years ago (Ma), than fossil and molecular clock data (∼80–90 Ma). Our results suggest that tip calibration may result in estimated dates that are more ancient than those obtained from other sources of data. This can be partially overcome by constraining the ages of internal nodes on the tree; however, when this was applied to our dataset, the estimated dates were still substantially more ancient than expected. We recommend that results obtained using tip calibration, and possibly morphological dating more generally, should be treated with caution.